Kinetic Model of Thermophilic Biohydrogen Production from POME - Md. Jahim, Jamaliah; Abdul, Peer Mohamed; Chu, Chen-Yeon; Wu, Shu-Yii; Takriff, Mohd Sobri; Harun, Shuhaida (International Journal of Integrated Engineering, 2019)
The study of fermentation kinetic parameters are crucial to understanding the environmental factors affect on biohydrogen production. Kinetic models for hydrogen production from anaerobic digestion of palm oil mill effluent (POME) by mixed culture were developed based on published work. The models accounted for substrate limitation, substrate inhibition, hydrogen production, and endogenous decay rate. Data from previous literature were used to compare four microbial growth kinetic models for hydrogen production in an ASBR system. The estimated values of the maximum specific growth rate (Î¼m) were found to be 0.371 h-1. In this study, the parameters of Y, kd, and B0 calculated were 2.64 gVSS/gCOD, 0.053 h-1, and 0.133 L H2/gCOD, respectively. The model fitting was found to be in good agreement with the experimental and can be utilized for the optimization and design of the process.